Anything but boring: A cultural criminological exploration of boredom. (August 2017) - Steinmetz, Kevin F; Schaefer, Brian P; Green, Edward LW
There is perhaps no experience in late modernity more universal than boredom . This analysis therefore responds to Ferrell's call to take boredom seriously in the study of crime and crime control. Our analysis of boredom draws from three separate qualitative analyses of police detectives, computer hackers, and prisoners serving life sentences to reveal boredom's influence across the criminological spectrum. Drawing from cultural criminology, this study frames boredom as a social condition that works in a dialectic with excitement. It rests betwixt and between the nuances of everyday life and saturates the periphery of experience among the three groups studied. Boredom is thus described as an inseparable component of the dynamics of crime and crime control under late modernity.